OSCILLATIONS OF INHOMOGENEOUS POROELASTIC LAYER WITH VOIDS - Alexander Ovanesovich Vatulyan; Denis Sergeyevich Shvedov (Advanced Engineering Research, 2013)
As part of the plane strain, the problem on steady oscillations of the inhomogeneous through-thickness isotropic poroelastic layer with voids is considered. The layer bottom is connected with the perfectly rigid foundation, the oscillations are caused by the surface stress on the top face. Under the known inhomogeneity laws for Lame parameter analogs – positive functions of the vertical coordinate – the layer oscillations are described by the system of three partial differential second-order equations with variable coefficients. Using the Fourier transform and some access statements, the problem is reduced to the system of three Fredholm integral equations of the second kind with continuous kernels. The numerical technique is proposed for identifying the transforms by the collocation method. The displacement vector and the relative volume are calculated using numerical inverse Fourier transform.